A method for preparing a sensitive material and sensor for VOCs gas sensor

By adding metal phase change energy storage microcapsules to the sensitive materials of VOCs gas sensors, the problem of sensitive films being prone to cracking or falling off in high temperature environments is solved, and the stability of the sensitive film and the accuracy of the detection results are improved.

CN114965601BActive Publication Date: 2025-04-29FEISI INSTR (SHENZHEN) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210521476.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-13
Publication Date
2025-04-29
Estimated Expiration
2042-05-13

AI Technical Summary

Technical Problem

After the sensitive materials of existing VOCs gas sensors are used in high temperature environments, the mechanical stability is reduced, resulting in the sensitive film being prone to cracking or falling off, affecting the accuracy of the detection results.

Method used

Using sensitive materials containing metal phase change energy storage microcapsules, the microcapsules are composed of nanozeolite powder and metal powder, and the capsule wall is a silica layer. They are prepared through sol-gel reaction to control the capsule core particle size and capsule wall thickness to improve performance stability.

Benefits of technology

By adding metal phase change energy storage microcapsules to sensitive materials, the heating and cooling rate is controlled, and the cracking and shedding of coating film caused by quenching and rapid heat is reduced, thereby improving the stability of the sensitive film and the accuracy of the detection results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114965601B_ABST
    Figure CN114965601B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of gas sensors, and specifically discloses a sensitive material for VOCs gas sensors and a method for preparing the sensor. The raw materials of the sensitive material for VOCs gas sensors include the following components by weight: 85-90 parts of tin dioxide; 4-6 parts of silicon dioxide; 0.4-0.8 parts of antimony trioxide; 0.5-1.5 parts of calcium fluoride; 1-2 parts of zirconium dioxide; 0.2-0.6 parts of palladium chloride; 3-5 parts of metal phase change energy storage microcapsules; the metal phase change energy storage microcapsules include a capsule core and a capsule wall, the capsule core is composed of nano zeolite powder and metal powder, the melting point of the metal powder is 100-400°C, and the capsule wall is a silicon dioxide layer. The sensitive material for VOCs gas sensors of the present application has the effects of high mechanical stability, not easy to crack and fall off.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of gas sensors, and in particular to a sensitive material for a VOCs gas sensor and a method for preparing the sensor. Background Art

[0002] The monitoring and control of toxic, harmful, flammable and explosive gases in the environment has become an environmental problem that people must solve, and gas sensors are a device to solve this problem. In recent years, with the development of the Internet and the Internet of Things and people's attention to air health, the demand for VOCs gas sensors has increased day by day, and the long-term stability of VOCs gas sensors is the main obstacle to the promotion and application of VOCs sensors. The instability of the sensor often brings certain errors to the detection results, causing the surrounding system to have underreporting, false alarms and other phenomena, which seriously hinders and restricts the practical application of VOCs sensors.

[0003] In the related technology, a sensitive material for detecting methanol gas is disclosed, which is a composite powder composed of SnO2, SiO2, PdCl2, Sb2O3, Pt, V2O5 and In2O3. The sensitive material is mixed with deionized water in a mass ratio of 1:2 to form a paste slurry, which is coated on the outer surface of a ceramic tube, placed in a constant temperature drying oven at 120°C for 1 hour, and then heat-treated in a muffle furnace at 400°C for 1 hour. The components are then welded and packaged and placed on an aging bench for aging to obtain a gas sensor.

[0004] With respect to the above-mentioned related technologies, the inventors believe that after the above-mentioned sensitive materials are used in a high-temperature environment for a long time, the mechanical stability of the sensitive film is reduced, causing the sensitive film to easily crack or fall off. Summary of the invention

[0005] In order to improve the stability of the sensitive film, the present application provides a sensitive material for a VOCs gas sensor and a method for preparing the sensor.

[0006] In the first aspect, the present application provides a sensitive material for a VOCs gas sensor, which adopts the following technical solution:

[0007] A sensitive material for a VOCs gas sensor, the raw materials of which include the following components in parts by weight:

[0008] 86-90 parts of tin dioxide;

[0009] 3-6 parts of silicon dioxide;

[0010] Antimony trioxide 0.3-0.8 parts;

[0011] Calcium fluoride 0.5-1.5 parts;

[0012] 1-2 parts of zirconium dioxide;

[0013] Palladium chloride 0.2-0.7 part;

[0014] 3-5 parts of metal phase change energy storage microcapsules;

[0015] The metal phase-change energy storage microcapsule comprises a capsule core and a capsule wall. The capsule core is composed of nano zeolite powder and metal powder, the melting point of the metal powder is 100-400° C., and the capsule wall is a silicon dioxide layer.

[0016] By adopting the above technical solution, the sensing mechanism of the gas sensor is: the surface of the sensitive material adsorbs the target gas, and the target gas molecules migrate from the surface of the membrane to the inside of the membrane, which causes the surface resistivity of the material to change. According to the change in surface resistivity, the concentration of the target gas is detected and calculated. The operating temperature of the VOCs gas sensor is generally around 400°C. Since metal phase change energy storage microcapsules are added to the sensitive material, the metal phase change energy storage microcapsules can absorb and release heat when the test environment heats up and cools down, thereby controlling the heating and cooling rates, reducing the cracking and shedding of the coating caused by rapid cooling and heating, and improving the stability of the sensitive membrane.

[0017] Optionally, the average particle size of the capsule core is 100 nm-100 μm, and the average thickness of the capsule wall is 50 nm-50 μm.

[0018] By adopting the above technical solution and controlling the particle size of the capsule core and the thickness of the capsule wall, metal phase change energy storage microcapsules with stable performance can be obtained.

[0019] Optionally, the metal powder is selected from tin, bismuth, and tin-bismuth alloy.

[0020] By adopting the above technical solution, the melting point of the above metal powder is between 100-400° C. and is suitable as a capsule core.

[0021] Optionally, the weight ratio of the nano zeolite powder to the metal powder is 1:(4-6).

[0022] By adopting the above technical solution, if the proportion of metal powder is too high or too low, the sensitive membrane is prone to cracking and falling off. Therefore, the weight ratio of nano zeolite powder to metal powder is preferably 1: (4-6).

[0023] Optionally, the method for preparing the metal phase change energy storage microcapsule comprises the following steps:

[0024] To prepare the capsule core, nano zeolite powder and metal powder are uniformly mixed, heated under the protection of inert gas to melt the metal powder, and after cooling and solidification, crushed to obtain the capsule core;

[0025] To prepare microcapsules, water, alcohol solvent and pH regulator are evenly mixed, capsule cores are added, and then ethyl orthosilicate is added to carry out sol-gel reaction, solid-liquid separation, washing and drying to obtain metal phase change energy storage microcapsules.

[0026] By adopting the above technical solution, after the metal powder is melted, it is wrapped on the surface of a ball of nano-zeolite powder to form a capsule core. The tiny gaps between the nano-zeolite powders provide deformation space for the metal powder, thereby improving the mechanical properties of the coating. After the sol-gel reaction of ethyl orthosilicate, a dense silica capsule wall is formed, thereby reducing the probability of melting and leakage of the metal powder.

[0027] Optionally, the pH adjuster is one or more of acetic acid, hydrochloric acid, ammonia water, and sodium hydroxide.

[0028] By adopting the above technical solution, the pH of the reaction system is adjusted, which is conducive to the smooth progress of the sol-gel reaction.

[0029] Optionally, the sol-gel reaction time is 12-48 hours, and the reaction temperature is 40-80°C.

[0030] By adopting the above technical solution, the embedding rate of the microcapsules is improved after sufficient reaction.

[0031] In a second aspect, the present application provides a method for preparing a sensitive material for a VOCs gas sensor, using the following technical solution:

[0032] A method for preparing a VOCs gas sensor comprises the following steps:

[0033] Step 1, mixing the above-mentioned VOCs gas sensor sensitive material with water evenly, grinding, and obtaining a slurry;

[0034] Step 2: evenly coat the slurry on the electrode surface of the VOCs gas sensor, dry and solidify, calcine, and assemble to obtain the VOCs gas sensor.

[0035] By adopting the above technical solution, metal phase change energy storage microcapsules are added to the sensitive material. The metal phase change energy storage microcapsules can absorb and release heat when the test environment heats up and cools down, thereby controlling the heating and cooling rates, reducing the cracking and shedding of the coating caused by rapid cooling and heating, and improving the stability of the sensitive film.

[0036] In summary, this application has the following beneficial effects:

[0037] 1. Since the present application adds metal phase change energy storage microcapsules to the sensitive material, the metal phase change energy storage microcapsules can absorb and release heat when the test environment is heated and cooled, thereby controlling the heating and cooling rates, reducing the cracking and shedding of the coating caused by rapid cooling and heating, and improving the stability of the sensitive film.

[0038] 2. In the present application, nano-zeolite powder is added to the capsule core. After the metal powder is melted, it is wrapped around the surface of a ball of nano-zeolite powder to form a capsule core. The tiny gaps between the nano-zeolite powders provide deformation space for the metal powder, thereby improving the mechanical properties of the coating. After the sol-gel reaction of ethyl orthosilicate, a dense silica capsule wall is formed, thereby reducing the probability of melting and leakage of the metal powder. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 is a SEM photograph of the sample made in Example 10 after the high and low temperature cycle test;

[0040] Figure 2 This is a SEM photo of the sample made in Example 2 after the high and low temperature cycle test. DETAILED DESCRIPTION

[0041] The present application is further described in detail below with reference to the embodiments.

[0042] Preparation example of metal phase change energy storage microcapsules

[0043] Preparation Example 1

[0044] The metal phase change energy storage microcapsule comprises a capsule core and a capsule wall, wherein the capsule core is composed of nano zeolite powder and metal powder, the capsule wall is a silicon dioxide layer, the average particle size of the capsule core is 100nm, and the average thickness of the capsule wall is 50nm. The preparation method of the metal phase change energy storage microcapsule comprises the following steps:

[0045] To prepare the capsule core, 10 g of nano zeolite powder and 40 g of metal powder are mixed evenly, wherein the nano zeolite powder is 4A type zeolite and the metal powder is tin powder, and the metal powder is heated under nitrogen protection to melt the metal powder, stirred evenly, cooled and solidified, and then crushed to obtain the capsule core;

[0046] To prepare microcapsules, 150 ml of water, an alcohol solvent and a pH adjuster were evenly mixed, wherein the alcohol solvent was 375 g of ethanol and the pH adjuster was 75 g of aqueous ammonia, the capsule core was added, and then 25 g of tetraethyl orthosilicate was added, the mixture was stirred evenly, and a sol-gel reaction was carried out. The reaction temperature was 80°C and the reaction time was 12 h. The mixture was separated into a solid and liquid state, washed and dried to obtain metal phase change energy storage microcapsules.

[0047] Preparation Example 2

[0048] The metal phase change energy storage microcapsule is different from the preparation example 1 in that the average particle size of the capsule core is 1 μm, and the average thickness of the capsule wall is 0.4 μm. The preparation method of the metal phase change energy storage microcapsule comprises the following steps:

[0049] To prepare the capsule core, 10 g of nano zeolite powder and 40 g of metal powder are mixed evenly, wherein the metal powder is tin powder, and the metal powder is heated under nitrogen protection to melt the metal powder, stirred evenly, cooled and solidified, and then crushed to obtain the capsule core;

[0050] To prepare microcapsules, 150 ml of water, an alcohol solvent and a pH adjuster were evenly mixed, wherein the alcohol solvent was 375 g of ethanol and the pH adjuster was 75 g of aqueous ammonia, the capsule core was added, and then 25 g of tetraethyl orthosilicate was added, the mixture was stirred evenly, and a sol-gel reaction was carried out. The reaction temperature was 60°C and the reaction time was 24 h. The mixture was separated into solid and liquid, washed and dried to obtain metal phase change energy storage microcapsules.

[0051] Preparation Example 3

[0052] The metal phase change energy storage microcapsule is different from the preparation example 1 in that the average particle size of the capsule core is 100 μm, and the average thickness of the capsule wall is 50 μm. The preparation method of the metal phase change energy storage microcapsule comprises the following steps:

[0053] To prepare the capsule core, 10 g of nano zeolite powder and 40 g of metal powder are mixed evenly, wherein the metal powder is tin powder, and the metal powder is heated under nitrogen protection to melt the metal powder, stirred evenly, cooled and solidified, and then crushed to obtain the capsule core;

[0054] To prepare microcapsules, 150 ml of water, an alcohol solvent and a pH adjuster were evenly mixed, wherein the alcohol solvent was 375 g of ethanol and the pH adjuster was 70 g of acetic acid. The capsule core was added, and then 25 g of tetraethyl orthosilicate was added. The mixture was stirred evenly and a sol-gel reaction was carried out. The reaction temperature was 40°C and the reaction time was 48 h. The mixture was separated into solid and liquid, washed and dried to obtain metal phase change energy storage microcapsules.

[0055] Preparation Example 4

[0056] The metal phase change energy storage microcapsule is different from that of Preparation Example 2 in that the metal powder is bismuth powder.

[0057] Preparation Example 5

[0058] The metal phase change energy storage microcapsule is different from that of Preparation Example 2 in that the metal powder is tin-bismuth alloy powder, and the tin-bismuth alloy is a commercially available tin-bismuth alloy with a melting point of 138°C.

[0059] Preparation Example 6

[0060] The metal phase change energy storage microcapsule is different from that of Preparation Example 5 in that the total mass of the capsule core is 50 g, and the weight ratio of nano zeolite powder to metal powder is 1:5.

[0061] Preparation Example 7

[0062] The metal phase change energy storage microcapsule is different from that of Preparation Example 5 in that the total mass of the capsule core is 50 g, and the weight ratio of nano zeolite powder to metal powder is 1:6.

[0063] Preparation Example 8

[0064] The metal phase change energy storage microcapsule is different from that of Preparation Example 5 in that the total mass of the capsule core is 50 g, and the weight ratio of nano zeolite powder to metal powder is 1:10.

[0065] Preparation Example 9

[0066] The metal phase change energy storage microcapsule is different from that of Preparation Example 5 in that the total mass of the capsule core is 50 g, and the weight ratio of the nano zeolite powder to the metal powder is 1:1.

[0067] Comparative Preparation Example 1

[0068] The metal phase change energy storage microcapsule is different from that of Preparation Example 2 in that the total mass of the capsule core is 50 g and the capsule core is tin powder.

[0069] Example

[0070] Example 1

[0071] A sensitive material for a VOCs gas sensor, the raw materials of which include the following components by weight:

[0072] Tin dioxide 86g;

[0073] Silicon dioxide 6g;

[0074] Antimony trioxide 0.8g;

[0075] Calcium fluoride 1.5 g;

[0076] Zirconium dioxide 2g;

[0077] Palladium chloride 0.7 g;

[0078] 3 g of metal phase change energy storage microcapsules, prepared according to Preparation Example 1.

[0079] Embodiment 2-9

[0080] A sensitive material for a VOCs gas sensor, which is different from Example 1 in that the metal phase change energy storage microcapsules are prepared in sequence from Preparation Examples 2-9.

[0081] Example 10

[0082] A sensitive material for a VOCs gas sensor, the raw materials of which include the following components by weight:

[0083] Tin dioxide 87.5 g;

[0084] Silicon dioxide 5g;

[0085] Antimony trioxide 0.6g;

[0086] Calcium fluoride 1g;

[0087] Zirconium dioxide 1.5g;

[0088] Palladium chloride 0.4 g;

[0089] 4 g of metal phase change energy storage microcapsules were prepared according to Preparation Example 1.

[0090] Embodiment 11

[0091] A sensitive material for a VOCs gas sensor, the raw materials of which include the following components by weight:

[0092] Tin dioxide 90g;

[0093] Silicon dioxide 3g;

[0094] Antimony trioxide 0.3g;

[0095] Calcium fluoride 0.5 g;

[0096] Zirconium dioxide 1g;

[0097] Palladium chloride 0.2 g;

[0098] 5 g of metal phase change energy storage microcapsules were prepared according to Preparation Example 1.

[0099] Example 12

[0100] A sensitive material for a VOCs gas sensor, which is different from Example 1 in that the weight of the metal phase change energy storage microcapsule is 1 g.

[0101] Example 13

[0102] A sensitive material for a VOCs gas sensor, which is different from Example 1 in that the weight of the metal phase change energy storage microcapsule is 10 g.

[0103] Embodiment 14

[0104] A method for preparing a VOCs gas sensor comprises the following steps:

[0105] Step 1: Mix the sensitive material for VOCs gas sensor with an appropriate amount of deionized water and grind for 30 minutes to obtain a slurry;

[0106] Step 2: Evenly coat the slurry on the electrode surface of the VOCs gas sensor, dry and solidify at 50° C., calcine at 350° C. for 2 h, and assemble to obtain the VOCs gas sensor.

[0107] Comparative Example

[0108] Comparative Example 1

[0109] A sensitive material for a VOCs gas sensor, which is different from Example 1 in that the metal phase change energy storage microcapsule is prepared by Comparative Preparation Example 1.

[0110] Comparative Example 2

[0111] A sensitive material for a VOCs gas sensor, the raw materials of which include the following components by weight:

[0112] Tin dioxide 90g;

[0113] Silicon dioxide 3g;

[0114] Antimony trioxide 0.3g;

[0115] Calcium fluoride 0.5 g;

[0116] Zirconium dioxide 1g;

[0117] Palladium chloride 0.2g.

[0118] Performance testing

[0119] Test methods

[0120] According to the method in Example 14, the VOCs gas sensors of Examples 1-13 and Comparative Examples 1-2 were made into VOCs gas sensors using sensitive materials as test samples.

[0121] (1) High and low temperature cycle test: In a nitrogen atmosphere, the temperature was increased from 20°C to 400°C at a heating rate of 5°C / min and kept constant for 10 min, and then the temperature was decreased from 400°C to 20°C at a cooling rate of 5°C / min and kept constant for 10 min. The number of cycles was 500. After the cycle, the appearance of the VOCs gas sensor was observed, and the cracking and shedding areas per unit area (1 square centimeter) were measured. The results are shown in Table 1.

[0122] (2) Acetone response-recovery time test: The response-recovery time of the test samples to acetone before and after the high and low temperature cycle test. The results are shown in Table 2.

[0123] (3) After the high and low temperature cycle test, SEM photos were taken of the surfaces of the samples prepared in Example 10 and Comparative Example 2.

[0124] Table 1 High and low temperature cycle test results

[0125]

[0126] Table 2 Response-recovery time test results of acetone

[0127]

[0128] Combining Examples 1-13 and Comparative Examples 1-2 and Table 1, it can be seen that when no metal phase change energy storage microcapsules were added to Comparative Example 2, after the cycle test, the coating had obvious cracks and obvious shedding, and the cracking and shedding area was as high as 15.2 square millimeters, indicating that the mechanical properties of the sensitive material coating were poor; when metal phase change energy storage microcapsules without nano zeolite powder were added to Comparative Example 1, after the cycle test, the coating had obvious cracks and obvious shedding, but the cracking and shedding area was 12.5 square millimeters, which was lower than that of Comparative Example 2, indicating that the addition of metal phase change energy storage microcapsules to the sensitive material After adding the metal phase change energy storage microcapsules without nano zeolite powder, the mechanical properties of the coating of the sensitive material can be improved. The possible reason is that the metal phase change energy storage microcapsules can absorb and release heat when the environment is heated and cooled, thereby controlling the heating and cooling rate and reducing the cracking and shedding of the coating caused by rapid cooling and heating; when the metal phase change energy storage microcapsules containing nano zeolite powder are added to Examples 1-3, after the cycle test, the coating has fine cracks, no shedding, and the cracking and shedding area is 3.5-3.7 square millimeters, which is greatly reduced compared with Comparative Example 1. The possible reason is that as the capsule core The tin powder easily causes the capsule wall to rupture when it expands due to heat, thereby causing the mechanical properties of the coating to decrease. In this application, tin powder and nano-zeolite powder are blended as capsule cores. The tiny gaps between the nano-zeolite powders provide deformation space for the tin powder. After the tin powder is melted, it can enter the tiny gaps between the nano-zeolite powders, thereby improving the mechanical properties of the coating. Among them, the performance of Example 2 is better; Example 5 uses tin-bismuth alloy as the metal powder. After the cycle test, the coating has fine cracks but no shedding, and the cracking and shedding area is 3 square millimeters, which further improves the mechanical properties of the coating. Preparation Examples 6-9 changed the weight ratio of nano zeolite powder and metal powder, and the cracking and shedding areas of the coatings changed. Among them, the proportion of metal powder in Example 8 was too high, and the cracking and shedding areas increased to 3.1 square millimeters. The proportion of metal powder in Example 9 was too low, and the cracking and shedding areas increased to 3.3 square millimeters. When Examples 6-7 were within the weight ratio range specified in this application, the cracking and shedding areas were 2.8-2.9 square millimeters. The mechanical properties of the coating of Example 6 were better, indicating that the weight ratio of nano zeolite powder to metal powder was preferably 1: (4-6). It can be seen from the results of Examples 10-13 that if the amount of metal phase change energy storage microcapsules added was too low or too high, the mechanical properties of the coatings were poor. Therefore, the amount of phase change energy storage microcapsules used was preferably 3-5 parts.

[0129] In combination with Example 2 and Table 1-2, it can be seen that in Comparative Example 1, metal phase change energy storage microcapsules without nano zeolite powder are added to the sensitive material, and in Example 2, metal phase change energy storage microcapsules containing nano zeolite powder are added to the sensitive material, which has little effect on the response time and recovery time of the VOCs gas sensor before the test; after the cycle test, the response time and recovery time of Comparative Example 1 and Comparative Example 2 are greatly increased, and the response time and recovery time of Example 2 are slightly increased, indicating that the sensitivity and recovery ability of Comparative Example 1 and Comparative Example 2 in detecting acetone gas are reduced, and the sensitivity and recovery ability of Example 2 in detecting acetone gas are basically unchanged. The reason is that the coatings of the sensitive materials of Comparative Examples 1 and 2 have cracks and fall off, resulting in the loss of sensitive materials, which in turn leads to a decrease in detection ability. The addition of metal phase change energy storage microcapsules in Example 2 can improve the temperature resistance and mechanical properties of the coating of the sensitive material.

[0130] Reference Figure 1-Figure 2 , Figure 1 This is a SEM photo of the sample made in Example 10 after the high and low temperature cycle test, with a magnification of 1000 times. It can be seen from the figure that there are no cracks or shedding on the surface of the coating film; Figure 2 This is a SEM photograph of the sample made in Example 2 after the high and low temperature cycle test, with a magnification of 2500 times. It can be seen from the figure that there is a large area of ​​shedding on the surface of the coating.

[0131] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A sensitive material for a VOCs gas sensor, characterized in that: The raw materials include the following components in parts by weight: 86-90 parts of tin dioxide; 3-6 parts of silicon dioxide; Antimony trioxide 0.3-0.8 parts; Calcium fluoride 0.5-1.5 parts; 1-2 parts of zirconium dioxide; Palladium chloride 0.2-0.7 part; 3-5 parts of metal phase change energy storage microcapsules; The metal phase-change energy storage microcapsule comprises a capsule core and a capsule wall. The capsule core is composed of nano zeolite powder and metal powder, the melting point of the metal powder is 100-400° C., and the capsule wall is a silicon dioxide layer.

2. The sensitive material for VOCs gas sensor according to claim 1, characterized in that: The average particle size of the capsule core is 100nm-100μm, and the average thickness of the capsule wall is 50nm-50μm.

3. The sensitive material for VOCs gas sensor according to claim 1, characterized in that: The metal powder is selected from tin, bismuth, and tin-bismuth alloy.

4. The sensitive material for VOCs gas sensor according to claim 1, characterized in that: The weight ratio of the nano zeolite powder to the metal powder is 1:(4-6).

5. The sensitive material for VOCs gas sensor according to claim 1, characterized in that: The preparation method of the metal phase change energy storage microcapsule comprises the following steps: To prepare the capsule core, nano zeolite powder and metal powder are uniformly mixed, heated under the protection of inert gas to melt the metal powder, and after cooling and solidification, crushed to obtain the capsule core; To prepare microcapsules, water, alcohol solvent and pH regulator are evenly mixed, capsule cores are added, and then ethyl orthosilicate is added to carry out sol-gel reaction, solid-liquid separation, washing and drying to obtain metal phase change energy storage microcapsules.

6. The sensitive material for VOCs gas sensor according to claim 5, characterized in that: The pH regulator is one or more of acetic acid, hydrochloric acid, ammonia water, and sodium hydroxide.

7. The sensitive material for VOCs gas sensor according to claim 5, characterized in that: The sol-gel reaction time is 12-48 hours, and the reaction temperature is 40-80°C.

8. A method for preparing a VOCs gas sensor, characterized in that: The following steps are involved: Step 1, mixing the sensitive material for the VOCs gas sensor according to any one of claims 1 to 7 with water, and grinding to obtain a slurry; Step 2: evenly coat the slurry on the electrode surface of the VOCs gas sensor, dry and solidify, calcine, and assemble to obtain the VOCs gas sensor.

Citation Information

Patent Citations

  • Phase transition thermal storage microcapsule paint containing tetradecyl alcohol and micron order metal powder

    CN104312305A

  • Microcapsule phase change particulate material doped with metal nano particles and preparation method of material

    CN105542724A